A Managed Risk: Mediated Musicianships in a Networked Laptop Orchestra. Issue 5 (2nd November 2018) - Valiquet, Patrick
Abstract : Mediation defers questions of meaning and power in a present situation to subjects, objects, times, or places which may not be present—or at least not in precisely the same way. Drawing upon ethnographic observations and interviews conducted with a new laptop orchestra at Concordia University in Montreal in 2011 and 2012, this article surveys some of the different ways that the concept of mediation can be used to foreground the politics of such technologically dense ensemble practices. Attending to the work of mediation in such contexts enables the ethnographic observer to follow the making and breaking of relations between an ensemble's sound, the practical interventions of players, instruments, instructors, and institutional patrons, and the wider political and aesthetic projections they make possible. The article concludes by providing a critical assessment of the laptop orchestra model on the basis of these observations.